In defense of partisanship - Zelizer, Julian E. (Columbia Global Reports, 2025)
"This book reimagines what partisanship might look like going forward from today. A new era of party-oriented reforms has the potential to pay respect the deep differences that divide us while simultaneously creating a more functional path on which two responsible political parties compete to shape policy while still being able to govern"--